Rapid Determination of Adenosine in Cordyceps by Online Extraction HPLC. (4th February 2019) - Qian, Zheng-Ming; Li, Chun-Hong; Song, Yue-Lin; Zhou, Miao-Xia; Li, Wen-Jia
Abstract: In this study, determination of adenosine in Cordyceps was accomplished by an online pressurized liquid extraction HPLC, and a poroshell column was employed for rapid HPLC separation. The Cordyceps sample powder was filled into a hollow guard column and extracted by thermal and pressurized water (75°C, 150 bar) for 3 min. Chromatographic separation was conducted on a poroshell 120 SB-Aq (4.6 × 50 mm, 2.7 μm) column and gradient elution was performed by water and methanol at a flow rate of 1.5 mL/min. The detection wavelength was set at 260 nm. The total measurement time including sample extraction and separation was <6 min. The calibration curve of adenosine was Y = 4.502 × 10 6 X + 1.731 × 10 4, which showed good linearity ( r 2 > 0.9993) within tested range (4.03–80.5 μg/mL). The intra- and inter-day precisions of adenosine were 0.24% and 0.94%, respectively, and the recoveries of adenosine was 96.1% (relative standard deviation, 4.49%). The validated method was then applied to determinate adenosine in six batches of Cordyceps, and the contents of adenosine were 0.28–0.48 mg/g. The developed method is beneficial for the quality control of Cordyceps .